2022
DOI: 10.1371/journal.pone.0273525
|View full text |Cite
|
Sign up to set email alerts
|

Does political participation help improve the life satisfaction of urban residents: Empirical evidence from China

Abstract: Studies have shown that political participation does not only affect the flow of public resources but also creates positive feedback on participants’ subjective perceptions. However, research on the relationship between political participation and the life satisfaction of Chinese urban residents is relatively scarce. Thus, this study investigates whether political participation helps improve the life satisfaction of Chinese urban residents. Based on 2577 samples of the 2015 Chinese Social Survey this study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
3
0
1
Order By: Relevance
“…26 Hence, urban locales, brimming with a plethora of engagements ranging from academia to politics, might appeal more to this demographic. 28 Age undeniably modulates happiness. While youth often radiates exuberance, the multifaceted ingredients of happiness morph across the age spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…26 Hence, urban locales, brimming with a plethora of engagements ranging from academia to politics, might appeal more to this demographic. 28 Age undeniably modulates happiness. While youth often radiates exuberance, the multifaceted ingredients of happiness morph across the age spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant positive correlation between national identity and both national pride and in-group preference (Zhang and Zuo, 2012). In addition, an individual's political values are closely related to their life satisfaction (He et al, 2022). This suggests that there is an indirect positive correlation between life satisfaction and patriotism.…”
Section: Gratitude General Life Satisfaction and Patriotismmentioning
confidence: 99%
“…This could be attributed to the observation that individuals with high life satisfaction often report strong cultural and ethnic identities (Vietze et al, 2019;Caqueo-Urízar et al, 2021), suggesting a symbiotic relationship between life satisfaction and identity (Dimitrova et al, 2018). Life satisfaction's significance extends to national legitimacy and political support (Chen and Shi, 2001;Tang, 2016;He et al, 2022), influenced by both institutional political characteristics (Radcliff, 2001;Skitka, 2005;Bjornskov et al, 2007) and individual values and judgments (Diener et al, 1985). Consequently, national attachment, including patriotism and nationalism, is positively correlated with national life satisfaction (Skitka, 2005;Bader, 2006;Liu et al, 2020).…”
Section: Cross-sectional and Longitudinal Mediating Role Of General L...mentioning
confidence: 99%
“…Although the CJP concept is new, its conceptual antecedent-political participation-was introduced in Verba et al's (1978) pioneering work and has since become well established. Following this groundbreaking study, political participation, defined as "activity that is intended to or has the consequence of affecting, either directly or indirectly, government action" (Verba et al, 1995, p. 9), has been used as an academic tool to capture public behavior related to politics (Ardèvol-Abreu et al, 2020;Chang, 2016;He et al, 2022;Ikeda et al, 2013;Pavlova et al, 2022). In this field, numerous studies have identified various determinants of political participation, including political efficacy (Heiss and Matthes, 2019;Ikeda et al, 2008;Jung et al, 2011), political knowledge (Gil de Zúñiga, 2012Johann, 2012;Lee et al, 2022), and media exposure (Pandey et al, 2020;Skoric et al, 2016;for review, Boulianne, 2020).…”
Section: Existing Studies and Their Limitationsmentioning
confidence: 99%